THE ETHICAL INFLUENCE LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Adrianto, Henricus Judi; Syafi'i, Muhammad; Gebang, Anthonius Yanto (Universitas Pembinaan Masyarakat Indonesia, 2024)
Human resources are the main asset for organizations who are planners and active actors of various activities within the organization. This research method uses quantitative research. The research results show that Ethic Leadership has a significant effect on the performance of Lubuk Pakam DPMD employees, where the t value is 3.762 while the t table is 1.699 (t count > t table and sig<0.05 (0.001<0.05). Thus it can be stated that ethics leadership has a significant effect on the performance of DPMD Lubuk Pakam employees. The work environment has a significant effect on the performance of Lubuk Pakam DPMD employees, with a t value of 2.986, while the t table is 1.699 (t count > t table) and sig<0.05 (0.006<0.05). Thus, it can be stated that the work environment has a significant effect on the performance of DPMD Lubuk Pakam employees. Simultaneous test results using the F valuetable 2,960, there are results where Fcount>Ftable (39.192>2.960) with a sig level<0.05 (0.000<0.05). On this basis, the previously proposed research hypothesis can be accepted because it is proven to be true. JEL Classification: M12, L25